Legal Study of Nominee Agreements in Villa Business Management: Perspectives of Decision No. 129/Pdt.G/2021/PN. Amp - Elvira Triana Putri; Surahmad (Dinasti Research, 2025)
In Indonesia, foreigners' land ownership is restricted by law. However, in practice, some foreigners legally own Indonesian land through a nominee agreement. This study aims to find out the importance of understanding legal protection for the parties involved in the nominee agreement, as well as the judge's considerations in deciding the case of villa business management with a nominee agreement in Decision No. 129/Pdt.G/2021/PN. Amp. The research method used is normative juridical which involves the analysis of regulations and cases related to land ownership by foreigners through nominee agreements, and through literature studies and data access through journals, as well as the Internet. The results of this study show that the form of protection for the parties involved in the nominee agreement is that the interests of the parties can be protected if there is a basis to prove when negligence occurs as a result of a legally made agreement. Then the judge's consideration in Decision No.129/Pdt.G/PN. Amp is indeed in accordance with the provisions applicable in Indonesia, but there is still a void regarding the regulation of ownership of land and buildings on it which if not regulated in the decision will have the potential to cause illegal control by foreign citizens.